Nutritional content of gluten free foods in the northern side of Cyprus - Zeybek, Sabiha Gökçen; Dayı, Taygun (Progress in Nutrition, 2022)
Background: Gluten free (GF) foods -which are the main part of the gluten free diets- are produced from grains without gluten protein. They have an important place in the food market. Depending of the type of GF foods, it may cause nutrient deficiencies in long term unconscious consumption. Nutrient deficiencies are related with some health problems thus evaluation of the GF foods contents has importance for the nutrition science. Methods and Study Design: The current study was conducted in Cyprus. Authors visited six diffirent supermarkets and determined 99 different gluten free foods. After the determination, they evaluated nutrient contents of GF foods from food labels and compared with reference foods which include gluten protein. They used TurKomp and BeBiS programme to determine reference foods nutrient content. Results: There were two main groups in this study. In the study group; there were 99 GF foods and 34 gluten containing foods in the control group. The mean energy, carbohydrate, fat, saturated fatty acid and sugar contents of the gluten free foods were higher, their protein contents were lower than control group (p